2019
DOI: 10.2147/dmso.s222271
|View full text |Cite
|
Sign up to set email alerts
|

<p>Association between glycated hemoglobin (HbA1c) and the lipid profile in patients with type 2 diabetes mellitus at a tertiary care hospital: a retrospective study</p>

Abstract: BackgroundTo investigate the association between glycated hemoglobin (HbA1c) and the lipid profile in patients with type 2 diabetes mellitus (T2DM) at a tertiary care hospital in Jeddah, Saudi Arabia (SA).MethodsThe present retrospective cross-sectional study was accomplished at the Faculty of Medicine, King Abdulaziz University (KAU), Jeddah, SA, between April and July 2018. There were 206 T2DM patients selected for the study (141 females and 65 males), and the data were collected through a review of the elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
3
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 17 publications
4
23
3
6
Order By: Relevance
“…13,15,16 However, Alzahrani et al and a few other studies reported a statistically non-significant negative link between HbA1c and HDL. 11,12,17 The present study found no relationship between HbA1c and LDL. Similar result reported in some studies, but there are studies inconsistent with the result which stated significant correlation between HbA1c and LDL.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…13,15,16 However, Alzahrani et al and a few other studies reported a statistically non-significant negative link between HbA1c and HDL. 11,12,17 The present study found no relationship between HbA1c and LDL. Similar result reported in some studies, but there are studies inconsistent with the result which stated significant correlation between HbA1c and LDL.…”
Section: Discussioncontrasting
confidence: 51%
“…Similar result reported in some studies, but there are studies inconsistent with the result which stated significant correlation between HbA1c and LDL. 11,13,[16][17][18] In the present study, T2DM patients in the group HbA1c ≥7% had significantly higher values of FBS, HbA1c, TG, TG/HDL levels compared to DM2 patients in DM2 HbA1c <7% group. These parameters showed a highly significant positive correlation in poor glycemic group with p≤0.00001.…”
Section: Discussionsupporting
confidence: 47%
“…The HbA1c level, although it represents a standard test for monitoring metabolic control, is not generally recommended for psoriatic patients in dermatological clinical practice. However, because HbA1c level reflects not only the glucose but also the lipid profile, 24 the reduction of these metabolic parameters in our patients, induced by apremilast, could be correlated to a decrease of HbA1c level. Altogether, these results suggest that this drug, by attenuating the systemic inflammatory state through the cAMP‐dependent PDE4 inhibition, may improve metabolic diseases associated with PsA.…”
Section: Discussionmentioning
confidence: 67%
“…In diabetic subjects, insulin resistance has been considered the reason for dyslipidemia. The causes for increased triglycerides levels in diabetic patients is an insu cient function or secretion of insulin that causes higher hepatic secretion of VLDL together with the late elimination of TG-rich lipoproteins, mostly due to greater substrate levels for TG synthesis [17].…”
Section: Discussionmentioning
confidence: 99%